Preloaded Descemet Membrane Endothelial Keratoplasty Grafts With Endothelium Outward: A Cross-Country Validation Study of the DMEK Rapid Device. Issue 4 (15th April 2021) - Wojcik, Gabriela; Parekh, Mohit; Romano, Vito; Ferrari, Stefano; Ruzza, Alessandro; Ahmad, Sajjad; Ponzin, Diego
Abstract : Purpose: To validate the "Descemet membrane endothelial keratoplasty (DMEK) Rapid" device for the cross-country transportation of preloaded DMEK grafts preserved with endothelium outward. Methods: DMEK grafts were stripped and loaded in the DMEK Rapid device with tissue culture medium (TCM) or transport medium (TM) with endothelium outward. The device was mounted in a 40-mL flask and preserved for 4 days on a rocker to simulate transportation (study A, n = 24) or shipped in the TM from Italy to the United Kingdom (study B, n = 9) and evaluated within 72 hours. All the tissues were stained with Alizarin red. Viability of the cells was checked postsimulations and posttransportation and was confirmed using live/dead staining. Expression of tight junction proteins was evaluated. Results: In study A, the endothelial cell loss observed from the TCM group was 20.8% (±5.2) compared with 19.5% (±6.7) from the TM group ( P = 0.41) after transport simulation. Alizarin red showed minimal uncovered areas in both groups. There were no statistical differences in viability between the TM (80.83%) and TCM groups (78.83%). In study B, 12.9% (±7.8) endothelial cell loss was observed after transporting the tissues from Italy to the United Kingdom with no significant difference between prestrip and posttransportation ( P = 0.05). Alizarin red staining did not show any uncovered area. Live/dead analysis showed 85.16% cell viability after transportation. zonula occludens-1 (ZO-1) was expressed in all tissues. Conclusions: The DMEK Rapid device is safe for preloading and shipping DMEK grafts internationally with endothelium outward within 72 hours when preserved in the transport media.